Improved admixture vaccine of fentanyl and heroin hapten immunoconjugates: Antinociceptive evaluation of fentanyl-contaminated heroin - Hwang, Candy S.; Smith, Lauren C.; Natori, Yoshihiro; Ellis, Beverly; Zhou, Bin; Janda, Kim D. (ACS Omega, 2018)
Fentanyl and its derivatives have become pervasive contaminants in the U.S. heroin supply. Previously, we reported a proof-of-concept vaccine designed to combat against heroin contaminated with fentanyl. Herein, we optimized the admixture vaccine and found that it surpassed the individual vaccines in every antinociceptive test, including a 10% fentanyl to heroin formulation. It is anticipated that other co-occurring drug abuse disorders may also be examined with admixture vaccines. © 2018 American Chemical Society.
Keywords: dept.che; peer-reviewed

A chemically contiguous hapten approach for a heroin-fentanyl vaccine. - Natori, Yoshihiro; Hwang, Candy S; Lin, Lucy; Smith, Lauren C; Zhou, Bin; Janda, Kim D (Beilstein journal of organic chemistry, 2019)
Background: Increased death due to the opioid epidemic in the United States has necessitated the development of new strategies to treat addiction. Monoclonal antibodies and antidrug vaccines provide a tool that both aids addiction management and reduces the potential for overdose. Dual drug vaccines formulated by successive conjugation or by mixture have certain drawbacks. The current study examines an approach for combatting the dangers of fentanyl-laced heroin, by using a hapten with one epitope that has domains for both fentanyl and heroin. Results: We evaluated a series of nine vaccines developed from chemically contiguous haptens composed of both heroin- and fentanyl-like domains. Analysis of the results obtained by SPR and ELISA revealed trends in antibody affinity and titers for heroin and fentanyl based on epitope size and linker location. In antinociception studies, the best performing vaccines offered comparable protection against heroin as our benchmark heroin vaccine, but exhibited attenuated protection against fentanyl compared to our fentanyl vaccine. Conclusion: After thorough investigation of this strategy, we have identified key considerations for the development of a chemically contiguous heroin-fentanyl vaccine. Importantly, this is the first report of such a strategy in the opioid-drug-vaccine field.
Keywords: Antinociception; Fentanyl; Hapten; Heroin; Vaccine; dept.che; peer-reviewed

Conjugate vaccine produces long-lasting attenuation of fentanyl vs. food choice and blocks expression of opioid withdrawal-induced increases in fentanyl choice in rats. - Townsend, E Andrew; Blake, Steven; Faunce, Kaycee E; Hwang, Candy S; Natori, Yoshihiro; Zhou, Bin; Bremer, Paul T; Janda, Kim D; Banks, Matthew L (Neuropsychopharmacology : official publication of the American College of Neuropsychopharmacology, 2019)
The current opioid crisis remains a significant public health issue and there is a critical need for biomedical research to develop effective and easily deployable candidate treatments. One emerging treatment strategy for opioid use disorder includes immunopharmacotherapies or opioid-targeted vaccines. The present study determined the effectiveness of a fentanyl-tetanus toxoid conjugate vaccine to alter fentanyl self-administration using a fentanyl-vs.-food choice procedure in male and female rats under three experimental conditions. For comparison, continuous 7-day naltrexone (0.01-0.1 mg/kg/h) and 7-day clonidine (3.2-10 mug/kg/h) treatment effects were also determined on fentanyl-vs.-food choice. Male and female rats responded for concurrently available 18% diluted Ensure R (liquid food) and fentanyl (0-10 mug/kg/infusion) infusions during daily sessions. Under baseline and saline treatment conditions, fentanyl maintained a dose-dependent increase in fentanyl-vs.-food choice. First, fentanyl vaccine administration significantly blunted fentanyl reinforcement and increased food reinforcement for 15 weeks in non-opioid dependent rats. Second, surmountability experiments by increasing the unit fentanyl dose available during the self-administration session 10-fold empirically determined that the fentanyl vaccine produced an approximate 22-fold potency shift in fentanyl-vs.-food choice that was as effective as the clinically approved treatment naltrexone. Clonidine treatment significantly increased fentanyl-vs.-food choice. Lastly, fentanyl vaccine administration prevented the expression of withdrawal-associated increases in fentanyl-vs.-food choice following introduction of extended 12 h fentanyl access sessions. Overall, these results support the potential and further consideration of immunopharmacotherapies as candidate treatments to address the current opioid crisis.
Keywords: *Analgesics, Opioid/ad [Administration & Dosage]; *Analgesics, Opioid/im [Immunology]; *Behavior, Animal/de [Drug Effects]; *Choice Behavior/de [Drug Effects]; *Drug-Seeking Behavior/de [Drug Effects]; *Fentanyl/ad [Administration & Dosage]; *Fentanyl/im [Immunology]; *Vaccines, Conjugate/pd [Pharmacology]; Adrenergic alpha-2 Receptor Agonists; Adrenergic alpha-2 Receptor Agonists/pd [Pharmacology]; Analgesics, Opioid; Animals; Article; Behavior, Animal; Choice Behavior; Clonidine; Clonidine/pd [Pharmacology]; CpG oligodeoxynucleotide; Drug-Seeking Behavior; Feeding Behavior; Feeding Behavior/de [Drug Effects]; Female; Fentanyl; Food; Male; Naltrexone; Naltrexone/pd [Pharmacology]; Narcotic Antagonists; Narcotic Antagonists/pd [Pharmacology]; Opioid-Related Disorders; Rats; Reinforcement, Psychology; Self Administration; Substance Withdrawal Syndrome; Substance Withdrawal Syndrome/pp [Physiopathology]; Tetanus Toxoid; Vaccines, Conjugate; alpha 2 adrenergic receptor stimulating agent; aluminum hydroxide; animal; animal behavior; animal experiment; animal model; antinociception; clinical effectiveness; clinical evaluation; clonidine; comparative study; controlled study; decision making; dept.che; drug conjugation; drug effect; drug infusion; drug seeking behavior; drug self administration; ensure; feeding behavior; female; fentanyl; fentanyl tetanus toxoid conjugate vaccine; food; food intake; immunology; male; naltrexone; narcotic analgesic agent; narcotic antagonist; nonhuman; opiate addiction; opioid use disorder; pathophysiology; peer-reviewed; priority journal; protein expression; rat; reinforcement; sodium chloride; tetanus toxoid; time to treatment; unclassified drug; vaccination; vaccine; withdrawal syndrome